2021
DOI: 10.3389/fonc.2021.695251
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Analysis of the ISUP Grade Group And Other Parameters in Prostate Cancer: Elucidation of Mutual Impact of the Various Parameters

Abstract: BackgroundProstate cancer has become increasingly common worldwide. Although Grade group (GG) is widely accepted as an indicator of prostate cancer grade, there are malignancies that cannot be defined by GG alone. Moreover, the relationship between GG and other parameters remains unclear. Herein, we aimed to explore the biological characteristics of prostate cancer.MethodsThis study included 299 radical prostatectomy cases. The Chi-square test and analysis of variance were used to analyze the association of GG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Imaging results such as CT/PET-CT and multiparametric MRI/PET-MRI had low sensitivity in identifying lymph node metastases ( 24 , 25 ). Nomograms had been built for predicting lymph node metastases ( 2 , 6 ); these tools also mainly relied on Gleason score and T stage, and we found that the two factors had an impact on the survival benefit of LND, and that extended LND was more likely to remove occult lymph node metastases, as higher Gleason score and T stage were risk factors for lymph node metastasis ( 26 28 ). We would like to point out that this study found Gleason score >8 and T stage >T3a was an indication for more lymph node yield.…”
Section: Discussionmentioning
confidence: 91%
“…Imaging results such as CT/PET-CT and multiparametric MRI/PET-MRI had low sensitivity in identifying lymph node metastases ( 24 , 25 ). Nomograms had been built for predicting lymph node metastases ( 2 , 6 ); these tools also mainly relied on Gleason score and T stage, and we found that the two factors had an impact on the survival benefit of LND, and that extended LND was more likely to remove occult lymph node metastases, as higher Gleason score and T stage were risk factors for lymph node metastasis ( 26 28 ). We would like to point out that this study found Gleason score >8 and T stage >T3a was an indication for more lymph node yield.…”
Section: Discussionmentioning
confidence: 91%
“…Second, many other prognostic factors, such as the lymphovascular invasion, has been known to be a poor prognostic factor for many cancers. However, we did not recorded the information of these factors in this study ( 31 ). Third, we could not promote a multidisciplinary treatment strategy for EMEC in this study, especially for advanced disease.…”
Section: Discussionmentioning
confidence: 99%
“…In a study that included 299 radical prostatectomy cases, Okubo et al showed that lymphatic invasion was independently associated with lymph node metastasis, whereas venous invasion was not. They recommended that lymphatic and venous invasion should be evaluated separately rather than being combined into the category of LVI [ 37 ]. Wilczak et al retrospectively analyzed pathological and clinical data from 14,528 consecutive patients who underwent radical prostatectomy and examined of the prognostic value of lymphatic invasion [ 21 ].…”
Section: Discussionmentioning
confidence: 99%